2021
DOI: 10.1007/s00262-021-02882-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific hormone changes during immunotherapy and its influence on survival in metastatic renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is a highly vascularized and immunogenic tumor, being an ideal candidate for checkpoint blockade-based immunotherapy. Accordingly, checkpoint inhibitors have demonstrated clinical efficacy in patients with metastatic RCC (mRCC). Sex-specific differences in cancer immunotherapy may be explained by the interaction of sex hormone signaling, genetic and environmental factors, affecting the innate and adaptive immune response in men and women in different ways. The aim of this prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Finally, as shown by Tulchiner et al., 37 patients treated with anti-PD1 could develop an increased LH-to-FSH ratio and estradiol levels. However, for an unknown reasons, this phenomenon seems to occur only in men.…”
Section: Secondary Hypogonadismmentioning
confidence: 77%
“…Finally, as shown by Tulchiner et al., 37 patients treated with anti-PD1 could develop an increased LH-to-FSH ratio and estradiol levels. However, for an unknown reasons, this phenomenon seems to occur only in men.…”
Section: Secondary Hypogonadismmentioning
confidence: 77%
“…However, the research also revealed that estrogen-induced Treg activation only existed in high level of estrogen. However, the result totally reversed in low estrogen level [ 92 ]. The similar result also showed that the differentiation of Th1 cells enhanced in low estrogen level, which promoted the Th1-induced CTL activation and up-regulated the anti-tumor immunity, while the high level of estrogen increased the proportion of Th2 phenotype, causing the immunity inhibition [ 58 ].…”
Section: Cancer Cellmentioning
confidence: 99%
“…Sexual health and dysfunction were measured by 33 multiple-choice questions pertaining to sexual interest, fatigue, satisfaction with sex life, orgasm difficulties, dryness (both vaginal and mouth), lubrication, and pain and discomfort in the multi-level Patient-Reported Outcomes Measurement Information System (PROMIS) Sexual Function and Satisfaction Measures questionnaire, a tool providing a comprehensive assessment of sexual function, satisfaction, and overall quality of life. [15][16][17][18][19][20][21] Three additional questions specific to the COVID-19 pandemic were included. Within the questionnaire, "sexual activity" was defined to include caressing, foreplay, masturbation, oral sex, vaginal/anal intercourse, and other forms of stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…To account for potential confounders, participants were asked about medication use outside of their lung cancer treatment and history of sexual dysfunction before their lung cancer diagnosis. Sexual health and dysfunction were measured by 33 multiple‐choice questions pertaining to sexual interest, fatigue, satisfaction with sex life, orgasm difficulties, dryness (both vaginal and mouth), lubrication, and pain and discomfort in the multi‐level Patient‐Reported Outcomes Measurement Information System (PROMIS) Sexual Function and Satisfaction Measures questionnaire, a tool providing a comprehensive assessment of sexual function, satisfaction, and overall quality of life 15–21 . Three additional questions specific to the COVID‐19 pandemic were included.…”
Section: Methodsmentioning
confidence: 99%